Shaping inclusiveness of a transportation system: Factors affecting seat-yielding behavior of university students in public transportation. (January 2022) - Baig, Farrukh; Zhang, Dong; Lee, Jaeyoung; Xu, Hongda
Abstract: The continuous increase in the elderly population and the need for disability-inclusive public transportation propelled authorities to implement policies to ensure seat availability for vulnerable users. Although most public transportation provides a few priority seats for vulnerable users, the seat availability problem remains due to its small quantity and its usage by normal passengers. To extend the theory of planned behavior (TPB), this study aims to evaluate how empathic concerns, attitude, injunctive norms, descriptive norms, and perceived behavioral control contribute to the behavioral intentions and actual conducts of yielding seats to vulnerable passengers with university students' survey responses in China. A partial least square path modeling based structural equation modeling (SEM) approach is employed to test the postulated hypotheses. Findings reveal that empathic concerns significantly promote the yielding seat intention and, thus, the actual conduct through its impacts on attitude, injunctive norms, and perceived behavioral control. This study also aims at capturing sociodemographic heterogeneity through multi-group comparison. It is found that a university student passenger who is older or more educated perceives greater control about seat yielding behavior, positively influencing their intention to yield their seat to a vulnerable person. In addition, less frequent public transportation usage is found to significantly accompany a higher tendency to yield a seat when required. The implications of "soft measures" to support the transportation policy for a sustainable and disability-inclusive public transportation service are discussed accordingly.